Reified Life : Speculative Capital and the Ahuman Condition - Narkunas, J. Paul (Book collections on Project MUSE., 2018)
'Reified Life' addresses the most pressing political question of the 21st century: what forms of life are free and what forms are perceived legally and economically as surplus or expendable, human and otherwise.